Penerapan Metode Analytical Hierarchy Process Dalam Komunikasi Pemasaran Pada Era New Wave Marketing - Ardhoyo, Novalia Agung Wardjito; Sunarto, Sunarto; Alifahmi, Hifni (Jurnal Pustaka Komunikasi, 2023)
The world is currently entering the Big Data era. Organizations take advantage of this moment and make it a tool for strategic business maneuvers. As was done by the modern Primago Islamic boarding school. All Primago marketing communication activities are mediated by social media. However, until now there is no formula model for setting priorities for their digital marketing communication activities. So the purpose of this research is (1) to find the priority model of choice in marketing communication activities through digital Primago. (2) To find the factors to be considered in designing an integrated digital marketing communication strategy for Primago. Theories that form the basis include Computer Mediated Communication, Information Integration Theory and the concept of Integrated Marketing Communications. The method used is a combination of quantitative and qualitative. The research results obtained are (1) The priority model of choice in designing Primago's digital marketing communication strategy is first managing the Website, simultaneously managing Facebook and Instagram, third managing YouTube and lastly is TikTok. (2) Factors to be considered in designing an integrated digital marketing communication strategy for Primago in building netizen cognitives response include Accessible, Affordable, Connectivity, Costumize and Real Time Measurement.